2019
DOI: 10.2499/p15738coll2.1335325
|View full text |Cite
|
Sign up to set email alerts
|

Deepening decentralization in Zambia: Political economy constraints and opportunities for reform

Abstract: established in 1975, provides research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition. IFPRI's strategic research aims to foster a climate-resilient and sustainable food supply; promote healthy diets and nutrition for all; build inclusive and efficient markets, trade systems, and food industries; transform agricultural and rural economies; and strengthen institutions and governance. Gender is integrated in all the Institute's work. Partnerships, communications, capacity st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…He suggests that such politicization of cities partially accounts for the country's poor and uneven record of urban service delivery (see also Masuku and Jili 2019). In a study of 16 councils in Zambia, including four city councils, Resnick et al(2019) detail the many ways in which elected ward councillors bypass the decisions of local bureaucrats or lobby the mayor to do so.…”
Section: Intra-council Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…He suggests that such politicization of cities partially accounts for the country's poor and uneven record of urban service delivery (see also Masuku and Jili 2019). In a study of 16 councils in Zambia, including four city councils, Resnick et al(2019) detail the many ways in which elected ward councillors bypass the decisions of local bureaucrats or lobby the mayor to do so.…”
Section: Intra-council Relationsmentioning
confidence: 99%
“…In the area of waste management, which involves a complex range of activities from separation, transport, disposal, destruction, and recycling, there have been a multiplicity of formal and informal actors involved and predictably, more mixed results. Many cities in the region, from Accra, Lusaka, and Maputo, tend to employ informal organizations and small-scale enterprises with minimal equipment, such as handcarts, to focus on collection in low-income neighbourhoods; large-scale private operators may target middle-income neighbourhoods and the public sector collects from central business districts (Grest et al 2013;Resnick et al 2019). The outcome, as shown in Ghana, can sometimes be unproductive competition, unequal outcomes, and a multiplicity of contracts from city governments with minimal accountability (Cities Alliance 2017).…”
Section: State-society Relations In Urban Governancementioning
confidence: 99%
See 1 more Smart Citation
“…We always contribute money towards garbage collection in this market, but the private waste collectors hired by cadres complain of not being paid on time. As a result, garbage is not collected on regular basis" (cited in Resnick, Siame, et al, 2019).…”
Section: Food Safety Oversight and Servicesmentioning
confidence: 99%
“…For instance, between 2008, when IFPRI's Malawi country program began, and 2020, the country's minister of agriculture has changed nine times, with a concurrent churning of directors and permanent secretaries. Using the case of Zambia, Resnick et al (2019) have shown that rapid and often unexpected turnover of civil servants within local government also affects service provision and bureaucratic morale.…”
Section: Bureaucratic Governancementioning
confidence: 99%